Knitting Tradition and Modernity: Reflections on the Role of Islamic Religious Education in the Global Era (International Forum of Researchers and Lecturers, 2025)
Islamic education faces significant challenges in the era of globalization, where technological advancements, secularization, and pluralism are reshaping the educational landscape. This study aims to analyze how Islamic education can weave tradition and modernity to remain relevant in the face of global dynamics. This research employs a qualitative approach using a literature review method, examining various sources related to Islamic education, globalization, and the integration of traditional and modern values. The findings indicate that Islamic education plays a strategic role in shaping the character and morality of Muslim generations while fostering an adaptive understanding of contemporary changes. Curriculum integration that combines religious and scientific knowledge, along with the utilization of technology in learning, emerges as a solution to maintain the relevance of Islamic education. Furthermore, the role of teachers as mediators between tradition and modernity is crucial to ensure contextual learning. The implications of this study highlight the need for a flexible curriculum, enhanced educator competencies, and collaboration between educational institutions, governments, and society to strengthen the Islamic education system amid the tides of globalization.